Socio-economic Determinants Influence on NiliRavi Buffalo Farmers Choice of Milk Marketing Channels in Punjab (Indian Journal of Extension Education, 2022)
A total of 120 NiliRavi buffalo farmers from two districts of Punjab were selected for the study. The average production, consumption and marketed surplus of the milk are found to be higher for the Firozpur farmers in comparison with their counterpart. About 70 per cent of NiliRavi farmers preferred organised marketing channels to dispose surplus milk. The distance of dairy cooperatives (Govt. or Private) / dairy FPOs with regular & assured market and support in availing loan for purchase of animals and inputs were main reasons for opting organised marketing channels. Advance payment for purchase of inputs and door step milk collection were important factors for choosing unorganised milk marketing channels. The results of binomial logistic regression revealed that Nili-Ravi farmer with younger age and large number of NiliRavi milch buffalo holdings preferred organised milk marketing channels to dispose surplus milk rather than unorganised channels. The organised milk marketing channels needs to be strengthened and promoted for regular and assured milk marketing and also use these channels as centre for the supply of NiliRavi superior germplasm to propagate their population.